Production of Green Diesel via Solvent-aided Deoxygenation of Methyl Oleate over Bimetallic NiCo/TiO2 Catalyst - Brandon Han Hoe Goh; Cheng Tung Chong; Jo-Han Ng (Chemical Engineering Transactions, 2024)
Commercialised biodiesel, comprising of methyl esters, have large amounts of oxygenated compounds which cause low calorific value, high viscosity, poor low temperature performance and can only used in blends with petroleum-based diesel. Deoxygenation of these compounds can occur through three reaction pathways which are decarboxylation, decarbonylation, hydrodeoxygenation. The removal of oxygen can improve their fuel properties, and is heavily influenced by the presence of hydrogen (H2). However, given safety issues during transportation and storage of H2, the use of solvents to produce in-situ H2 for the deoxygenation process has been suggested as an alternative. The present work attempts to investigate the addition of solvents (deionised water, methanol, ethanol, 1-propanol, 2-propanol, n-hexane and cyclohexane) on the deoxygenation of methyl oleate to enhance its fuel properties. The experiments were carried out with unreduced bimetallic NiCo impregnated onto TiO2. Incorporation of NiCo onto TiO2 maintained the mesoporous nature of the support while increasing the number of strong acid sites of the catalyst, which can promote C-O bond cleavage during deoxygenation. Under hydrogen-restricted conditions, the deoxygenation is expected to occur mainly through decarboxylation and decarbonylation to produce alkanes and alkenes, with cracking to produce shorter chain methyl esters. The deoxygenation was conducted with 50 g methyl oleate, 40 g solvent, 5 wt% catalyst at 300 °C for 2 h in a pressurised nitrogen atmosphere. GCMS analysis show that the addition of 2-propanol showed the highest methyl oleate conversion (69.08 %) over other solvents, with 12.74 % selectivity for alkane formation. These results indicate the potential of solvent-aided deoxygenation of methyl esters for biofuel use.